Jeremiah: prophecy in a time of crisis : an introduction and study guide - Mills, Mary E. (T & T Clark study guides to the Old Testament, 2020)
Introduction -- Reading the book of Jeremiah -- Historical criticism and the study of Jeremiah -- The continuing role of historical critical enquiry -- The move to rhetorical criticism -- Terror, pain and chaos: the rhetorical focus on Jeremiah -- Bodies, space and excess as conceptual tools for reading Jeremiah -- Jeremiah: theology, story, history.